2022
DOI: 10.1002/ecs2.4042
|View full text |Cite
|
Sign up to set email alerts
|

Nuanced qualitative trait approaches reveal environmental filtering and phylogenetic constraints on lichen communities

Abstract: We propose that a qualitative trait approach based on more detailed nuanced traits may reveal previously overlooked patterns, especially when combined with phylogenetic perspectives. By sampling epiphytic lichens and using a functional approach based on nuanced qualitative traits, such as a much greater resolution over photobiont identity, type of cortex, and chemical compounds, we evaluated the effects of environmental filtering and phylogenetic constraints on community assembly along a natural succession of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…A CCM is thought to be important in concentrating inorganic carbon in low‐CO 2 environments, and the switch to algae with a CCM could play a role in mitigating prolonged water saturation and inhibited CO 2 diffusion in lichen thalli. However, in aquatic algae the convergent loss of a CCM is associated with low‐light conditions (Raven, 2003) and indeed, the absence of a CCM in lineages such as Trentepohliales may explain their predominance in low‐light environments (Koch et al ., 2022).…”
Section: Evolution After Symbiosis Establishmentmentioning
confidence: 99%
“…A CCM is thought to be important in concentrating inorganic carbon in low‐CO 2 environments, and the switch to algae with a CCM could play a role in mitigating prolonged water saturation and inhibited CO 2 diffusion in lichen thalli. However, in aquatic algae the convergent loss of a CCM is associated with low‐light conditions (Raven, 2003) and indeed, the absence of a CCM in lineages such as Trentepohliales may explain their predominance in low‐light environments (Koch et al ., 2022).…”
Section: Evolution After Symbiosis Establishmentmentioning
confidence: 99%
“…This approach likely owes its success to the outsized effect of the pyrenoid‐containing genera Trebouxia and Asterochloris , especially among nontropical macrolichens, that has masked the physiological diversity of eukaryotic lichen photobionts. More recently, renewed attention has been given to the differences between Trentepohlia and chlorococcoid green algal lichen distributions (Käffer et al, 2021; Koch et al, 2022), and it is tempting to continue such an approach rather than using genus‐level photobiont identification. However this simple clade‐based distinction is still not mechanistic, overlooking the absence of CCMs in major chloroccoid genera such as Symbiochloris .…”
Section: Discussionmentioning
confidence: 99%
“…However, these broad categories mask considerable variation in physiology, in particular within the chlorococcoid green algae. Indeed, recent work has found that finer scale, genus‐level photobiont occurrence is associated with environmental changes during forest succession (Koch et al, 2022). These fine‐scale responses align with the presence or absence of CCMs.…”
Section: Introductionmentioning
confidence: 99%
“…These anatomical adaptations are not, however, universal and have been convergently lost in multiple algal lineages, especially in terrestrial/subaerial environments (e.g., Trentepohlia , Symbiochloris ). Lichenized algae lacking CCMs are therefore more susceptible to carbon limitation by water saturation (Palmqvist et al, 1997) but potentially more tolerant of low light (Koch et al, 2022) and better able to utilize water vapor (Phinney et al, 2019), with consequences for distributions along environmental gradients (Koch et al, in press).…”
Section: Setting the Scenementioning
confidence: 99%
“…Water relations are driven not only by WHC, but also by rates of water acquisition and loss. Water‐holding capacity may be impacted by surface properties (Lakatos et al, 2006) and photobiont physiology (Phinney et al, 2019; Koch et al, 2022), while the latter may be quite responsive to thallus temperature and therefore albedo (color/albedo studies). It is also important to recognize that not all potential traits will be universally applicable.…”
Section: Mechanistic Understandingmentioning
confidence: 99%